Wealth Taxation as an Instrument of Fiscal Justice: Legal and Policy Analysis - Fryandi Simanullang; Norma Yulita Sari (Pemuliaan Keadilan, 2026)
Inequality in Indonesia remains significant, particularly due to the concentration of wealth among high-net-worth individuals (HNWIs). Emphasizing the importance of addressing this disparity can motivate policymakers to pursue equitable solutions, thereby promoting social justice through wealth taxation. Using a literature review and an empirical legal approach, this research analyzes relevant regulations, policy discussions, and academic literature on wealth taxation in Indonesia. The study also evaluates institutional readiness and potential challenges in implementing such a policy. The results indicate that the wealth tax has considerable revenue potential, ranging from IDR 54 trillion to IDR 155.3 trillion, depending on the tax model applied. Highlighting this potential can empower policymakers and foster optimism about the tangible benefits of implementing such a policy.